Beyond technique in solution-focused therapy : working with emotions and the therapeutic relationship - Lipchik, Eve. (New York : Guilford Press, 2002)
Publisher's description: Solution-focused therapy is often misunderstood to be no more than the techniques it is famous for--pragmatic, future-oriented questions that encourage clients to reconceptualize their problems and build on their strengths. Yet when applied in a'one-size-fits-all' manner, these techniques may produce disappointing results and leave clinicians wondering where they have gone wrong. This volume adds a vital dimension to the SFT literature, providing a rich theoretical framework to facilitate nonformulaic clinical decision making. The focus is on how attention to emotional issues, traditionally not emphasized in brief, strengths-based interventions, can help'unstick' difficult situations and pave the way to successful solutions. Written by leading practitioner and SFT codeveloper Eve Lipchik, the book will enhance the work of novice and experienced clinicians alike.
Includes bibliographical references and index.
Keywords: Solution-focused therapy